Spores Morphological Characteristics of Several Ophioglossaceae and Psilotaceae Fern in "Eka Karya" Botanical Garden - Bali - Pramesti, Ni Kadek Rika; Lestari, Wenni Setyo; Kriswiyanti, Eniek; Wijaya, I Made Saka (Jurnal Biodjati, 2023)
Ferns of Ophioglossaceae and Psilotaceae families can be found in the "Eka Karya" Botanical Garden, Bali as a collection or naturally growing in the botanical garden and those families are taxonomically classified as primitive ferns. The morphological characteristics of the family of Ophioglossaceae and Psilotaceae or even other types of ferns can be known through the morphological characteristics of the spores. This study aimed to characterize the spore morphology of the Ophioglossaceae and Psilotaceae fern of The "Eka Karya" Botanical Garden. Observation of the morphological characteristics of spores in the "Eka Karya" Botanical Garden was carried out by a simple method without acetolysis. The result of six types of fern plants from the family of Ophioglossaceae and Psilotaceae showed similarities to the spore unit, monads. Each family has unique characteristics that can be used to differentiate each other. The family Ophioglossaceae has a variety of spore colors, trilete spore types, mostly globose-shaped (except for one species the trilobate), the average polar diameter is 28.59±2.19 – 31.00±2.49 μm and the equatorial diameter is 32.85±1.74 – 37.55± 1.71 μm, the P/E ratio is 0.79-0.87, the shape based on the P/E ratio is suboblate, the spore size category is medium and has radial symmetry. For the family Psilotaceae, has a pale yellow-green spore color, monolete type, elongate-ellipsoidal shape, average polar diameter of 26.20±2.76 –29.81±2.96 μm and equatorial diameter of 52.98±2.55 – 63.31±4.65 μm, P/E ratio of 0.47-0.49, shape based on P/E ratio i.e. peroblate, large spore size category and has bilateral symmetry. Those characteristics are valuable taxonomic data that can be used as diagnostic characters for the identification of the families Ophioglossaceae and Psilotaceae.